Tara! Sugbu a campaign proposal on domestic tourism in the Philippines for ages 18 to 30 residing in Metro Manila - San Andres, Michaela Angela A.
"Positive affect enhances creativity, making you more likely to find new solutions for the problems you meet, both in work and in private life. It also supports social bonds, meaning that you will be more open to other people, and other people will tend to like you more." -Ruut Veenhoven, Dutch Sociologist. Travelling is an integral part of life. Everyone of us wants to travel and go to somewhere new. Searching for these pleasurable experiences that some might say that we have to attain in order to feel happiness and satisfaction in life. All of us have our own preferences in all of things. What dictates our preferences is something that is based on our knowledge and what we're exposed to. This study tackles the current state of domestic tourism in our country and how to further improve it. Most of the Filipinos assumes that they know and already experienced the Philippines and would rather travel abroad first before exploring their own home. Much more enthusiastic and learning the foreign culture than knowing one's culture first. Although despite that, there are still some fellow countrymen that would want to travel and explore their own home before branching out. It is time to show these people who supports our country that what they chose is the right thing. With these audiences, pro abroad and pro Philippines, what we need to do is to showcase that there are still a lot of untouched beautiful destination in our country that not everyone is aware of. These are the places that needs to be brought into light for the Filipinos to explore and experience. Going to these places will immerse them to the different culture Philippines has which will lead for them to love and appreciate more our country. For them to get to know themselves as Filipinos and to know what really their home is.